2021
DOI: 10.1111/ecc.13490
|View full text |Cite
|
Sign up to set email alerts
|

Being assigned a clinical nurse specialist is associated with better experiences of cancer care: English population‐based study using the linked National Cancer Patient Experience Survey and Cancer Registration Dataset

Abstract: Objective: This study aimed to examine whether being given the name of a clinical nurse specialist (CNS) is associated with better cancer patients' experiences across different points along their cancer care pathway.Methods: We identified 100,885 colorectal, lung, breast and prostate cancer patients who responded to the National Cancer Patient Experience Survey between 2010 and 2014. We compared experiences of four key aspects of cancer care among patients who reported being given a CNS name with those who did… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 25 publications
1
16
0
Order By: Relevance
“… 6 , 53 , 57 , 60 In the UK, two studies of the role of clinical nurse specialists in cancer care found that contact with them was subsequently associated better experiences of involvement in treatment decisions, care co-ordination and being treated with more respect and dignity. 64 , 65 Furthermore, better experiences in terms of the patient-provider relationship were also found to improve adherence to office visits for colorectal cancer surveillance in USA. 57 In addition patients who reported that their self-goal of treatment was to cure their cancer rather than to control it reported better experiences with access to care, coordination of care, respect for patient preferences, communication, and emotional support.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“… 6 , 53 , 57 , 60 In the UK, two studies of the role of clinical nurse specialists in cancer care found that contact with them was subsequently associated better experiences of involvement in treatment decisions, care co-ordination and being treated with more respect and dignity. 64 , 65 Furthermore, better experiences in terms of the patient-provider relationship were also found to improve adherence to office visits for colorectal cancer surveillance in USA. 57 In addition patients who reported that their self-goal of treatment was to cure their cancer rather than to control it reported better experiences with access to care, coordination of care, respect for patient preferences, communication, and emotional support.…”
Section: Resultsmentioning
confidence: 97%
“…Older patients, those from more socioeconomically deprived areas, those with the worse performance status, multiple comorbidities, and patients diagnosed via emergency presentation were under-represented in CPES. Alessy et al., 2021 64 Being assigned a clinical nurse specialist is associated with better experiences of cancer care: English population-based study using the linked National Cancer Patient Experience Survey and Cancer Registration Dataset Population-based cross- sectional study using 2010 - 2014 CPES data linked with cancer registration data in England for colorectal, lung, breast, and prostate cancers. To assess whether being assigned a clinical nurse specialist is associated with better cancer patients' experiences 2 Patients who reported being given the name of a CNS in the CPES reported better care experiences on four aspects of care: involvement in treatment decisions, care coordination, treatment with respect and dignity, and overall care experience.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical nurse specialists (CNS) play a key role in coordinating cancer care, contributing to the cancer multidisciplinary team, as well as in providing information and emotional support for individual patients during face-to-face and telephone contact 12–16. Previous reports have shown variation in access to CNS by geography and by tumour site 17 18. The National Cancer Patient Experience Survey (CPES) asks patients about a wide range of care aspects including their experiences with CNS 19.…”
Section: Introductionmentioning
confidence: 99%
“…The National Cancer Patient Experience Survey (CPES) asks patients about a wide range of care aspects including their experiences with CNS 19. CNS care has been shown to play a role in patients’ receipt of anticancer therapy and in improving experiences of patients with cancer with other care aspects such as care coordination, involvement in treatment decisions and overall care experiences 18 20. An important question is whether variation in care experiences of patients with cancer with CNS is also associated with their survival.…”
Section: Introductionmentioning
confidence: 99%